Changes and analysis of anti‐HBs titres after primary immunization in 1‐ to 16‐year‐old Chinese children: A hospital‐based study. Issue 4 (29th November 2017) - Yue, X.; Ge, C.; Zhuge, S.; He, H.; Yang, H.; Xu, H.; Huang, A.; Zhao, Y.
Summary: Immunization with the hepatitis B vaccine is the most effective measure to prevent Hepatitis B Virus (HBV) infection. The aim of this study was to investigate the change in antibody levels induced by administration of the hepatitis B vaccine in children aged 1‐16 year old in a large sample sized investigation. HBV markers were determined in 93 326 1‐ to 16‐year‐old hospitalized children who completed primary immunization as infants from south‐west China, Chongqing. Analyses were performed on anti‐HBs titre changes with increasing age, and the revaccination effect was evaluated in children aged 7‐14. The percentage of protective antibody was between 45.29% and 63.33% in all age groups, but was higher in the 1‐, 2‐ and 3‐year‐old groups (90.31%, 83.95% and 71.82%, respectively), and the rate of high‐responder was 5.03%‐10.56%, except in the 1‐year‐old group (23.33%). Additionally, 3.33%‐25.79% of subjects had not seroconverted. There was no significant difference in antibody levels between girls and boys ( P  > .05). The Geometric Mean Titers in children with confirmed revaccination history were significantly higher than those with unknown or no revaccination history ( P  < .0001). In conclusion, the overall rate of protective anti‐HBs was 67.10% with consecutive age groups from 1 to 16, it decreased from 90.31% to 45.29% for 1‐ to 8‐year‐old individuals, and interestingly, the rate increased from 45.46% to 63.33% for subjects aged 9‐15. Anti‐HBs titres were significantly improved after revaccination. Booster doses are recommended for those without seroconversion, especially children who live in school with other students or have family members with positive HBsAg.